Assessment of sexual identity, sexual-behavior and self-reported medical and psychosocial issues of men who have sex with men in Chandigarh, India - Sharma, Anjali; Das, Karobi; Saini, Sushma Kumari; Ghai, Sandhya; Mittal, Sandeep; Kaur, Manmeet (International Journal Of Community Medicine And Public Health, 2020)
Background: Men who have sex with men (MSM) are a vulnerable group who are susceptible to high incidence of Sexually Transmitted Infections (STIs) and Acquired Immuno-Deficiency Syndrome (AIDS). The objective of the study was to assess sexual identity, sexual behavior and self-reported medical and psychosocial issues of MSM in Chandigarh, India. Methods: A total 115 MSM were included in the study from two Non-Governmental Organization (NGO) centres of Chandigarh and were selected using simple random sampling. The interview was conducted in the office of NGOs centre with the help of an interview schedule. Results were analysed using descriptive analysis. Results: Nearly half of the participants (48.7%) self-reported their identity as bisexual and 27.8% of them identified them as Kothi (passive partner). Approximately one third of (33.9%) MSMs reported their first sexual relationship as ‘non-consensual’ and 19.1% reported themselves as a victim of child abuse. Six percent participants reported symptoms of depressed mood, 22.6% of MSMs had suicidal thoughts and 11.3% had tried to attempt suicide at least once. STIs symptoms were reported by 15.6% of the participants in the last three months; while 2.6% were HIV positive. Conclusions: Psychosocial issues and health problems are triggering factors for suicidal ideation and suicidal attempt in the MSM population.